(untitled) (Conference on English Language Teaching, 2024)
The presence of innovation-based discourse learning applications, especially English Language Speech Application (ELSA), human-made intelligence (computer-based intelligence) can advance EFL students’ speaking performance. This exam seeks to analyze the speaking performance of EFL students by utilizing the ELSA speaking application, further investigate their insights, and find out the inhibiting variables that influence their low performance in speaking. This exploration configuration uses qualitative descriptive techniques. Aimed at finding out students’ views on using the ELSA application in learning English speaking skills. The population in this review consists of secondary school students in Indonesia. Meanwhile, the example of this review is 20 middle school students who were interviewed and 6 students who had to explain their perceptions in using ELSA Speak. Remembering that previously students had involved the ELSA application as a learning medium to develop ways of expression in English subjects. In collecting information, experts used a survey consisting of four questions. The questions that scholars ask depend on educational methods that are most effective for articulating EFL. Based on the results, 13 students agreed that using the ELSA application to practice speaking English could help them and students also agreed that the ELSA application could also increase student independence in learning anytime and anywhere by utilizing technology in education. The ELSA application was created to overcome problems student; 74% of respondents agreed with this statement and agreed that the ELSA application works with speaking guidance. In addition, the scientist asked students simple questions in a work to identify weaknesses in the ELSA application. Because the app’s voice input uses Google Voice, some students said they anticipated the voice would sound like a local speaker.